Investigating attitudes towards medication and barriers to self-management among Hungarian adults with diabetes mellitus: A cross-sectional study. - Klára Bíró; Mihály Varga; Viktor Dombrádi; Nóra Kovács; Attila Nagy; Gábor Bányai; Klára Boruzs (PLoS ONE)
The key to effective patient care is the patient's proper cooperation, so it is important to examine the beliefs about medicine and self-management among diabetes patients. Therefore, the primary aim of the study was to investigate the attitude toward metformin medication and self-management of adult patients with diabetes in Hungary. A total of 591 metformin-taking diabetes patients completed the Beliefs about Medicine Questionnaire, while 283 metformin-taking diabetes patients completed the Environmental Barrier Assessment Scale. Multivariate regression analysis was conducted to investigate which socio-demographic factors influence the beliefs regarding medicines and various environmental barriers to diabetes self-management. Participants who reported a good or very good financial status were more likely to feel the need to take metformin compared to those perceiving bad or very bad financial status (coef = 0.25; p = 0.020). Respondents between 55-64 years and those older than 65 were significantly less concerned about metformin than those aged 18-24 years (coef = -0.47; p = 0.028 and coef = -0.41; p = 0.047). Participants with secondary education were significantly less likely to think that metformin was harmful than those with primary education (coef = -0.50; p = 0.009). In addition, those aged 35 or older saw more barriers to taking medication than those aged 18-24 years (35-44: coef = -0.54; p = 0.020; 45-54: coef = -1.15; p < 0.001; 55-64: coef = -1.06; p < 0.001; 65 years or older: coef = -1.48; p < 0.001). Also, significant negative association was found for several factors (such as age, education, self-reported financial status, subjective health status) with barriers regarding exercise. Overall, socio-demographic factors significantly impact both the attitude toward medicine and diabetes self-management. However, the impact considerably varies according to different beliefs and environmental barriers. To further improve drug adherence and self-management for diabetes, doctors should take into consideration the relevant socio-demographic factors when communicating with their patients.